Æthelred II 'the Unready' and the Role of Kingship in Gunnlaugs saga Ormstungu: 2019 Winner of the Society for Court Studies Annual Essay Prize. (2nd January 2020) - Firth, Matthew
Abstract : Episodes of travel to foreign courts are a feature of Íslendingasögur — Icelandic family sagas. It is a trope particularly ubiquitous of the skáldasögur — poets' sagas — where a skáld's reputation as warrior and hero is augmented through interactions with historical figures of the Scandinavian world. The resultant depictions of various cultures and societies are one of the interesting features of the corpus. The late thirteenth-century Gunnlaugs saga provides a notably rich exemplar of the motif of the travelling skáld . The hero, Gunnlaug Illugason, travels widely, visiting the royal courts of England, Viking Dublin and Sweden, alongside various non-royal courts including that of Norway. Of particular interest is the portrayal of Æthelred II (978–1016) and the English court, which is not only at odds with the depictions of other courts within the narrative, but with the historical tradition of Æthelred's fraught kingship. This article examines the differing portrayals of kingship within Gunnlaugs saga, questioning how Icelanders perceived English rulers in contrast to their Scandinavian counterparts, and whether Æthelred's characterisation as a good king is authorial invention, or remnant cultural memory of his kingship.